A Dibenzoazacyclooctyne as a Reactive Chain Stopper for [2]Rotaxanes. Issue 21 (8th June 2017) - Hou, Zhan‐Yao; Yeniad, Bahar; Van Guyse, Joachim; Woisel, Patrice; Mullen, Kathleen M.; Rutjes, Floris P. J. T.; van Hest, Jan C. M.; Hoogenboom, Richard
Abstract : A strained dibenzoazacyclooctyne (DIBAC) derivative was introduced for the preparation of a rotaxane by strain‐promoted azide–alkyne cycloaddition (SPAAC), also referred to as a copper‐free click reaction. The DIBAC can efficiently act as a bulky reactive chain stopper to transform a pseudorotaxane architecture consisting of a diazo‐functionalized dialkoxynaphthalene guest and a tetracationic cyclobis(paraquat‐ p ‐phenylene) (CBPQT 4+ ) host into the corresponding [2]rotaxane. Furthermore, the use of the DIBAC is demonstrated to be limited to short rigid macrocycles, as it is unable to act as stopper for a rotaxane featuring a larger crown ether macrocyclic host. Abstract : A strained dibenzoazacyclooctyne (DIBAC) derivative is introduced for the preparation of a rotaxane by a "threading‐followed‐by‐stoppering" strategy through the strain‐promoted azide–alkyne cycloaddition (SPAAC), a popular copper‐free click reaction; the results reveal that this DIBAC derivative is large enough to act as stopper.